2018
DOI: 10.1016/j.jneb.2018.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Food Choice Drivers in the Context of the Nutrition Transition in Delhi, India

Abstract: Young adult women in Delhi seem to rely on preferences of their families, habits and perceptions established in childhood, convenience, and food safety and health when making choices about food. These aspects of decision-making should be targeted in future interventions aimed at improving dietary intake in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…Older participants in this study also demonstrated that other (non-parent) family members were important influences around their dietary practices. These findings corroborate those from a recent study among Indian women, who reported that in trying to make them happy, they often ate food that they knew their spouses and children preferred [49]. Food in Uganda, as in many other SSA countries, is an identifier of cultural heritage and tradition.…”
Section: Discussionsupporting
confidence: 88%
“…Older participants in this study also demonstrated that other (non-parent) family members were important influences around their dietary practices. These findings corroborate those from a recent study among Indian women, who reported that in trying to make them happy, they often ate food that they knew their spouses and children preferred [49]. Food in Uganda, as in many other SSA countries, is an identifier of cultural heritage and tradition.…”
Section: Discussionsupporting
confidence: 88%
“…Currently, many nutrition programs target mothers of young children to improve infant and young child feeding practices (understandably), but more effort and innovation is needed to improve consumer knowledge and awareness more generally, such as through media campaigns, school-based interventions and public-private partnerships to improve marketing and advertising for nutritious foods. Furthermore, chemical contamination of vegetables and fruits with pesticide residues or artificial cosmetic enhancement is a growing consumer concern in India (Bailey et al, 2018). For consumer demand to increase for these foods, public trust in food safety is essential, necessitating enforcement of basic food quality standards (Umali-Deininger & Sur, 2007).…”
Section: Marketing and Promotion Strategies For Healthy Dietary Divermentioning
confidence: 99%
“…It is also necessary for individuals and persons responsible for household food purchasing and the preparation of meals to make nutritious food choices. The factors that influence individual decision-making around food are many and varied and have social, environmental, and psychological dimensions [92][93][94][95]. The research literature on value chains and diet quality included a wide range of interventions that aimed to improve the desirability of nutritious food (Table 4).…”
Section: Impact Pathways Related To Increasing Nutritious Food Choicesmentioning
confidence: 99%